Multi-channel MAC protocol based on network partitioning for wireless sensor networks - Bin CHENG; Lin-lin CI; Cheng-ping TIAN; Ming-hua YANG (Tongxin xuebao)
The limited amount of available orthogonal channels and noise interference are two major issues to constrain performances of multi-channel MAC protocols in wireless sensor networks (WSN).In conjunction with features of data gathering networks,a partitioning-based multi-channel MAC protocol was designed.Initially it partitioned network into several sub-trees with lower collision factor,without increasing the total value of interference around the whole network.Furthermore,it adopted a coarse-grained channel assignment strategy on basis of graph coloring theory,in order to ensure each sub-tree work on a relative optimal channel.Simulation results show that the proposed MAC protocol can significantly improve throughput and reduce end-to-end latency and packet loss.